Food systems and health - Shostak, Sara (Advances in medical sociology ;, 2017)
In recent years, the ways in which food is produced, distributed, and consumed have emerged as prominent health and social issues. With rising concern about rates of obesity, food systems have attracted the attention of state actors, leading to both innovative and controversial public health interventions, such as citywide soda bans, "veggie prescription" initiatives, and farm-to-school programs. At the same time, social movement activism has emerged focused on issues related to food and health, including movements for food justice, food safety, farm worker's rights, and community control of land for agricultural production. Meanwhile, many individuals and families struggle to obtain food that is affordable, accessible, and meaningfully connected to their cultures. Volume 18 of Advances in Medical Sociology brings cutting-edge sociological research to bear on these multiple dimensions of food systems and their impacts on individual and population health. This volume will highlight how food systems matter for health policy, health politics, and the lived experiences and life chances of individuals and communities.